# Answer to Question #6224 in Geometry for Tiffany

Question #6224

6x+1=3x+6?

Expert's answer

substract 3x from both parts of the equation:

6x+1=3x+6

-3x -3x

3x+1=6& now substract 1 from both parts

& -1 & -1

3x=5

hence x=5/3

6x+1=3x+6

-3x -3x

3x+1=6& now substract 1 from both parts

& -1 & -1

3x=5

hence x=5/3

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment